Prevalence of Multi-drug Resistant Acinetobacter baumannii (MDRAB) in Amman Jordan During 2018 - El-khatib, Layla; Al-Dalain, Saed; Al-Matarneh, Rama; Al-Bustanji, Sara; Al-Dmour, Marwa; Al-Amarin, Yara; Gaber, Yasser (Infectious Disorders - Drug Targets, 2021)
Purpose: Acinetobacter baumannii is an opportunistic pathogen, and is among the most problematic nosocomial infections as well as community-acquired infections. This retrospective study was conducted as an attempt to determine the prevalence of multidrug-resistant A. baumannii (MDRAB) isolates from the north and central Jordan area during 2018. Methods: Patients’ records provided by an accredited central private laboratory located in Amman, were examined for A. baumannii isolates identified during this period. The isolates were identified to the species level using the API-10S system and the antimicrobial sensitivity testing was determined using the Kirby–Bauer disc diffusion method. Results: A total of 43 unduplicated isolates were obtained and classified according to clinical sampling source into: Group I (blood), Group II (urine) and Group III (wound, pus, sputum, bedsore and others). Total MDRAB isolates recorded were 29 (67.4 %). Resistance to imipenem was found to be 36% and 94% among groups II and III, respectively, and resistance to meropenem was 60% and 88% among the same groups, respectively. Conclusion: Antimicrobial stewardship programs at a national scale are needed to calculate the actual proportion of MDRAB in the country and to combat its increasing emergence and decrease the magnitude of antibiotic resistance.
Keywords: resistance